The St. Louis Equation: "Democratic" and "Republican" Versions and Other Experiments - Silber, William L. (The Review of Economics and Statistics, 1971)
T HE equation developed by the Research Department of the Federal Reserve Bank of St. Louis to explain changes in GNP ' has had a considerable impact on the thinking of monetary economists. It has, in particular, reinforced the position of those who contend that monetary policy has a powerful impact on GNP. On the other hand, serious doubts arise according to the basic St. Louis equation as to the efficacy of the fiscal impact on GNP. There have been a, number of comments on the St. Louis equation which presented alternative specifications of the basic reduced-form equa,tion for GNP.2 In general, these formulations have revealed a more powerful role for fiscal policy while the strength of monetary policy remained unaltered. Most of these reformulations of the St. Louis equation have specified different monetary and/or fiscal variables than those used by St. Louis. This has given rise to disputes between researchers as to the appropriate monetary and fiscal variables 3 to use in these equations. In this paper the results of various experiments with the basic St. Louis equation using the St. Louis variables are presented. In other words, the question asked here is: given the use of the same exogenous policy variables as St. Louis are there any changes in the basic regressions which would alter the conclusion regarding the efficacy of monetary and fiscal policy? The results reported below suggest that alternative specifications of the basic St. Louis equation do produce significantly different implications for the efficacy of fiscal policy. In particular, a straightforward division of the sample period produces Republican and Democratic St. Louis equations with the associated monetary and fiscal multipliers.